2016
DOI: 10.1111/are.13049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water temperature on the physiology of fish spermatozoon function: a brief review

Abstract: Motility is a key factor in function of the spermatozoon and determines semen quality and fertilizing capacity. Effective motility occurs when sperm is diluted in a swimming solution, the adequacy of which is determined by factors varying according to fish species. Spermatozoon motility rate and velocity, as well as duration of the motility period, are influenced by the temperature of the water in which broodfish are held. Increase in temperature of swimming medium beyond the optimal increases cell metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 86 publications
(128 reference statements)
1
41
0
1
Order By: Relevance
“…It has been demonstrated that the duration of motility is temperature dependent and species specific [56][57][58]. In cyprinids, it was shown that extracellular and intracellular pH, as well as the ionic composition of the swimming media, influences the initiation and duration of sperm motility [59].…”
Section: Evaluation Of Fish Sperm Motility Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that the duration of motility is temperature dependent and species specific [56][57][58]. In cyprinids, it was shown that extracellular and intracellular pH, as well as the ionic composition of the swimming media, influences the initiation and duration of sperm motility [59].…”
Section: Evaluation Of Fish Sperm Motility Parametersmentioning
confidence: 99%
“…Fish species are adapted to a large variety of temperatures (from several degrees below 0 to 40-50°C). Low temperature could represent an adverse factor for sperm to fertilize eggs because decreasing the temperature reduces the flagellar beat frequency and consequently the sperm translational velocity [57]. This is probably compensated by the increase motility duration observed when temperature is decreased [57,58,119], the latter increasing statistically the chances of egg-sperm meeting.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Sperm of most external fertilization fish species is immotile in the testis and seminal plasma and motility is induced when in contact with the aquatic environment during natural reproduction or with activating agent during artificial reproduction. External factors such as osmolality, the presence of ions (K + , Na + , Ca 2+ ), pH and temperature influence the activation of sperm motility (Dadras et al, ; Dzyuba & Cosson, ). In freshwater species, the main external factor that activates sperm motility is the reduced osmolality of the extracellular media, as previously described in cyprinids (Cosson, ).…”
Section: Introductionmentioning
confidence: 99%